SYNTHESIS AND SCREENING OF SOME AZOMETHINES BEARING METHYL SALICYLATE MOIETY FOR ANTIBACTERIAL ACTIVITIES - Chanda, Sumitra; Baluja, Shipra (Indonesian Journal of Pharmacy, 2016)
In this study, the series of novel azomethines were synthesized from methyl salicylate and their structural determination was done by IR, NMR and mass spectral data. The screening of these synthesized compounds were done against some Gram positive and Gram negative bacteria in DMF and DMSO solvents by agar disc method. It is observed that solvent and compound structure both affect the inhibition. DMF is found to be good solvent in the present study. Amongst all studied compounds, JB-4 showed maximum zone of inhibition against most of the studied bacterial strains while compound JB-2 is least effective. Thus, substitution affects inhibition and methyl salicylate moiety with cinnamaldehyde side chain is most effective. Further, virtual screening of these compounds was done to evaluate molecular properties and bioactive scores of these compounds.Keywords: azomethines, methyl salicylate, antibacterial activity, agar disc method, DMF, DMSO